Écriture imitative – écriture artistique ou « artisanale » ? Histoires de femmes au collier de velours - Wandzioch, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2019)
The anonymous story entitled Histoire prodigieuse d’un gentilhomme auquel le diable est apparu, et avec lequel il a conversé sous le corps d’une femme morte, advenue à Paris le 1 janvier 1613, published in 1613, became a source of inspiration for Washington Irving and, later, for several French writers, including Petrus Borel, Paul Lacroix, Alexandre Dumas, and Joseph Méry. They plagiarized the American author’s text and, in this sense, it would be exaggerated to call them artists. In fact, their imitations resemble rather an artisan work, except for Alexandre Dumas’ novel which, despite numerous borrowings, attests to originality and, for this reason, its author deserves to be named an artisan of art.